Comparison of intubating laryngeal mask airway and fiberoptic bronchoscopy for endotracheal intubation in patients undergoing cervical discectomy - Kolli S Chalam; Jyothi Gupta (Wolters Kluwer Medknow Publications, 2016)
Background and Aims: Direct laryngoscopy is hazardous in patients with cervical posterior intervertebral disc prolapse (PIVD) as it may worsen the existing cord compression. To achieve smooth intubation, many adjuncts such as fiberoptic bronchoscope (FOB), video laryngoscopes, lighted stylets, and intubating laryngeal mask airways (ILMAs) are available. However, there is a paucity of literature comparing ILMA with fiberoptic intubation in patients with PIVD. Hence, this study was designed to compare the effectiveness of ILMA technique with FOB to accomplish endotracheal intubation in patients undergoing cervical discectomy. Material and Methods: Sixty patients of age group 20-60 years, of American Society of Anesthesiologists status I or II, were enrolled in this prospective and randomized study. They were allocated to one of the two groups, ILMA group and FOB group. The patients were intubated orally using either equipment, after dexmedetomidine premedication and induction of general anesthesia. Chi-square and Fisher exact tests were used to find the significance of study parameters on a categorical scale. Paired samples t-test and Student's t-test were used to find the significance of study parameters on a continuous scale. Significance was assessed at 5% level of significance. Results: Bronchoscopy was a faster method of securing airway as compared with ILMA (38.13 ± 11.52 vs. 29.83 ± 13.75 s). Tracheal intubation was successful in all 60 patients (100%), belonging to both groups. Conclusion: ILMA and FOB were comparable with regards to ease of intubation in terms of time, the number of attempts and hemodynamic stability.